Anda di halaman 1dari 12

# 1.

1
Warm-up Practice:
A.
1. 1, 3, 5, 7; 19; 29

## 8. 0, , 2/3, ; 9/10; 14/15

9. 0, , 2/5, ; ; 14/17

## 12. -1, 2, -3, 4; 10; -15

B.
13. 32

14. 33

15. 208

16. 9/10

C.
17. An = 2n 1

18. An = 2n

19. An =

20. An =

; An = 1 +

21. An = 3n 2

22. An =

23. An = 2n x (-1)

n-1

;An = 2n x (-1)

n+1

25. An = -3n + 2
n

An =
; An = 1

n+1

26. An = -4n + 3
n/2

27. An = (5) ; 5

28. An = n + n

D.
29. 63

30. 126

## 32. 17/4, 4 1/4

33. -13/15

34. 5/12

E.
35. 2 + 4 + 6 + 8 + 10 + 12 = 42

36. 1 + 4 + 7 + 10 + 13 + 16 + 19 + 22 = 92

## 37. 0 + + 2/3 + + 4/5 = 163/60; 2 43/60

38. 1 + 1 + 1 + 1 +1 = 5

39. -1 + 1 1 + 1 1 + 1 = 0

F.

3

## 43. 1/x , 1/x , 1/x , 1/x , 1/x , 1/x

2

42. x, x , x , x , x , x

44. x, 2x , 3x , 4x , 5x

## 45. 1/x, 4/x , 9/x , 16/x , 25/x

46.

Powerplus
A.
1. (x + 1) + (x + 2) + (x + 3) + (x + 4)
4

2. (x 3) + (x 4) + (x 5) + (x 6)
5

3. (x + 1) + (x + 1) + (x + 1) + (x + 1) + (x + 1) + (x + 1)
5.

6.

4. (x + 3) + (x + 3) + (x + 3) + (x + 3)

B.
1.

2.

3.

4.

5.

6.

7.

8.

9.

10.

11.

12.

13.

14.

C.
2 is True. (walang page 14, na ulit yung 13)
D.
a.
n
1
2
3
4
5

F1 + F2 + . Fn
1
2
4
7
12

F1 + F2 + . Fn
1
2
6
15
40

Notice that:
1.
2.

F1 + F2 + . Fn = Fn + 2 1
2
2
2
F1 + F2 + . Fn = FnFn + 1

Fn + 2 1
1
2
4
7
12

FnFn + 1
1
2
6
15
40

b.
2
n+1

n
1
2
3
4
5

FnFn + 2 + (-1)
1
4
9
25
64

1
4
9
25
64

Yes.
Proof by Induction:
2

2

2

n+1=

## We know that Fn = Fn + 2 Fn + 1 . Subsitute, we get

2
n+1=

( Fn + 2 Fn + 1) Fn + 2 1

2
n+1=

2
n+2=

2
n+2=

Fn + 1(Fn + 1 + Fn + 2) + 1

F
F
F
F

n+2

- Fn + 1Fn + 2 1

n+1+

Fn + 1Fn + 2 + 1

But, Fn + 1 + Fn + 2 = Fn + 3 , so,
2
n+2=

2F

## Fn + 1Fn + 3 + 1. So, 1 implies 2. Let n + 1 = a, where a is even, since n is odd. Similarly,

2
a+2=

( Fa + 3 Fa + 2) Fa + 3 + 1

2
a+2=

2
a+2=

2
a+3=

Fa + 2(Fa + 2 + Fa + 3) 1, but Fa + 2 + Fa + 3 = Fn + 4 .

F
F
F
F

2
a+3

- Fa + 2Fa + 3 + 1

2
a+3+

Fa + 2Fa + 3 + 1

3. F a + 2 = FaFa + 3 2 1. => F n + 3 = Fn + 2Fn + 4 1. We know that n + 3 is even. Therefore, the equation will have + 1 when n is
even and 1 when n is odd. We can denote that as:
2
n+1=

1.
2.
3.
4.
5.

## 5. (37 + 38, 24 + 25 + 26, 13 + 14 + 15 + 16 + 17, 10 + 11 + 12 + 13 + 14 + 15,3 + 4 + 5 + 6 + 7 + 8 + 9 + 10 + 11 + 12)

7747
1
5
10

1.2
A.
1. Arithmetic; d = 1

2. Arithmetic; d = 3

3. Not Arithmetic

4. Arithmetic; d = 4

5. Arithmetic; d = 5

6. Not Arithmetic

7. Not Arithmetic

8. Arithmetic; d =

9. Arithmetic; d = 2/3

## 10. Not Arithmetic

B.
11. an = 5n 3

12. an = 3n + 8

13. an =

14. an = 10n 6

15. an = 3n 6

16. an = 4n 9.4721

C.
17. 76

18. 9/2

19. 16.207

20. 43/5

21. 1

22. 37

23. 5

24. 8.4

D.
25. 16

26. 15

27. 46

28. 13

29. 21

30. 14

E.
31. 10

32. 21

33. 96

34. 44

35. 1220

36. 210

37. 3775

38. 765

F.
42, 44, 46 are true.

Powerplus
A.
1. 8, 13, 18; 88; Sum = 816

## 3. 2, -1, -4; -85; Sum = -1245

4. 4, 2, 0; -74; -1400

## 6. -2, -4, -6; -200; Sum = -10100

B.
1. 396

2. 504

3. 1275

4. 3488

5. -27

6. -65

7. 3888

8. 320

9. 7

10. 630 cm

11. No. The last row will contain 3 blocks, and there will be a total of 9 rows.
12. 6

13. P7100

14. P465

15.

a.

b.
y(x + z) = 2xz

y(x + z) = 2xz

xy + yz = 2xz
xy xz = xz yz
x(y z) = z(x y)

17. 579

18. 99

19.
20. Sn =

= 3n 1
2 + an = 6n 2
an = 6n 4

= 3n n

## Take the Challenge

1.
2.
3.
4.
5.

40
78
92
166 ( not sure )
45

SECTION 1.3
Warmup Practice
A.
1. Geometric; ratio = 5

2. Geometric; ratio = 2

4. Not geometric

5. Not geometric

## 6. Geometric; ratio = -1/3

7. Geometric; ratio = -2

8. Not geometric

## 10. Geometric; ratio = x/2

B.
11. 10, 5, 5/2, 5/4, 5/8

## 16. 5, -25, 125, -625, 3125

17.

18. c, b,

, 2a, 4b,

C.
19. 3, 6, 12, 24, 48

22. 8, 4, 2, 1,

D.
33. 728

34. 381

35. 33

36. -728

37. -64.5

## 38. -85/24 or -3 13/24

E.
39. 1093

40. 55987

41. 547

42. 171

43. 31

44.33/32 or 1 31/32

45. 26/81

Powerplus
A.
1. 1/16

2. -1/125

3. -1

4. -1

5. 32; 62 +

6. 81; 121 +

7. 2

8.

9. 3584

10. 1/32

11. 1/27

12.

13. -3

14.

17. -16

18. 27

19. Impossible

20. 5

B.
1.

sq. units

2. 2047

## 3. 163.604 or 40951/250 4. Approximately 1286.831681 m

Take the Challenge
1.

28.

2.

=
2

b.

## . By the difference of squares property, we have:

n

have 1 + 9 + 9 + . + 9 =
3.
4.

. But, 9

n+1

=3

2n + 2

.So, we have:

=
. Next, we

-516096
a. First, we know that r% = 0.01r. Also,let T0 be the starting value of the quantity. So, r% of T0 = 0.01r x T0. So, T1 = T0 +
2
0.01r x T0 = T0(1 + 0.01r). Similarly, we have T2 = T1(1 + 0.01r) = T0(1 + 0.01r) . So, this means that T1 , T2 , T3 , . Tn
n
form a geometric sequence with common ratio (1 + 0.01r) and Tn = T0(1 + 0.01r) .
8,144,473.134.

5.
6.

1139
No integral value of x.

Section 1.4
Warmup Practice
A.
1. 24

2. 4

3. No sum

4. 3

5. 1/4

6. No sum

7. 8/49

8. 8/7

9. 2

10. -1/7

B.
11. 1/3

12.2/3

13. 31/99

14. 5/11

15. 2 410/999

16.3 1/37

17. 29/225

18. 5/6

C.
19. 20 cm

20.120 cm

21. 30 cm

22. 24 cm

Powerplus
A.

1. -1/2

2.

3. a1 = 1; r = 1/3

4. 21/8

B.
1. d3 = 7.2; d5 = 6.48; d2n 1 = 8 x 0.9
2. d4 = 8.1; d2n = 10 x 0.9
n

3. a. 80(1 - 0.9 )

C.
n

b. 100(1 0.9 )

4. 190

1. a. 1/2

(n 1)

b. 10 cuts

(n 1)

2. a. P1P2 = a cm;P2P3 =

cm;P3P4 = a cm

b. Since QP1R is an isosceles right triangle, and all the cuts are perpendiculars, then P1P2 = 2P3P4 = 4P5P6 = . So, this
geometric sequence has common ratio of . Also, P2P3 = 2P4P5 = 4P6P7 = . Finally, we have P1P2 = P2P3 . So, we have P1P2 =
P2P3 = 2 P3P4 = 2 P4P5 = . So, this is a geometric sequence with common ratio 1/ or

c.a(2 + ) cm
Take the Challenge
1.

a.

cm

b.2 +

cm

c. s = or
2. a. OP2 = 5 cm; A1 = 25 cm
b. A2 =

cm

c. i. ratio =
ii. 50 cm

iii. We know that since OPnPn + 1 is an isosceles triangle, we know that OPn + 1 = PnPn + 1 =
A1 = (OPn + 1) (PnPn + 1) = (
2

2

3. 15/8 mm
4. a. 40 cm
b. 40 cm
c. 400/3 cm

## OPn ) = ()(OPn ) = (ln)

Section 1.5
A.
1. 5/23, 5/26, 5/29

B.
1. 1/ 79

2. 2/23

3. 1/18

## 4. Not a harmonic sequence

OPn. Also,

Powerplus
A.
1. Impossible. The terms of an arithmetic sequence are 2/5, 1/5, 0, - 1/5, - 2/5. However, taking the reciprocals of each will
result in one having an undefined value.
2. 12/11, 12/7, 4, - 12
3. 12/25, 6/19
4. 1/5, 1/8, 1/11
5. 1/10; 2/n
6. , 1/3, , 1/5, .
7. 9 and 1
8. 2
9. 6 and 24
10. It is given
Take the Challenge
1. First, since m and n are in a harmonic progression, then 1/m and 1/n are in an arithmetic progression. Let a be the first term
in that sequence. So,
1/m = a + (n 1)d => 1 = am + dm(n 1), and
1/n = a + ( m 1)d => 1 = an + dn(m 1). Subtracting the second from the first, we get
1 1 = am an + dm(n 1) dn(m 1) => 0 = a(m n) + dmn dm dmn + dn => 0 = a(m n) d(m n) => 0 = (a d)(m n).
We know that m n, so, we have a d = 0 or a = d. Substituting to any of the equations (both will yield the same result, but for
st
the sake of this solution lets use the 1 equation.)
1/m = a + (n 1)d = a + (n 1)a = an => a = 1/mn.
Now, using the formula to get the (m + n)th term, we have a + (m + n 1)d = a + (m + n 1)a = a(m + n) =

## So, this is the

(m + n)th term of the arithmetic progression so that its reciprocal is the harmonic progression given. Therefore, the (m + n)th
term of the harmonic progression is

2. Since a, b and c are terms of a harmonic progression, 1/a, 1/b and 1/c are corresponding terms of an arithmetic progression.
Let such an arithmetic progression have a general formula of a + (k 1)d. So,
1/a = a + (p 1)d.(i)
1/b = a + (q 1)d (ii)
1/c = a + (r 1)d..(iii)

## (i) (ii) gives 1/a 1/b = a + pd d a qd + d = (p q)d => (b a) = (p q)d x ab(iv)

(ii) (iii) gives 1/b 1/c = a + qd d a rd + d = (q r)d => (c b) = (q r)d x bc(v)
(iii) (i) gives 1/c 1/a = a + rd d a pr + d = (r p)d => (a c) = (r p)d x ac.(vi)
Adding (iv), (v), and (vi) yields
(b a) + (c b) + (a c) = (p q)d x ab + (q r)d x bc + (r p)d x ac
0 = d[(p q)ab + (q r)bc + (r p)ac]. But d 0, so
bc(q r) + ca(r p) + ab(p q) = 0, which gives out the desired result.
3. 6 and 3
4.
5.
Section 1.6
A.
1. 6

2. 120

3. 2

4. 1

5. 45

6. 84

7. 7

8. 28

9. 20 10. 11

B.
5

6

4 2

3 3

2 4

5

16

12

3 2

2 3

8

4 4

2 3

2 8

4 2

3 3

2 4

## 23. 27x + 54x y + 36x y + 8y

2 2

4 2

2 4

22. 8x 12x y + 6x y y

12

18.
3

6

## 16. x + 12x y + 60x y + 160x y + 240x y + 192xy + 64y

19. y - 4y + 6y 4y + 1
4 2

24.
6

25.

6

29. a

4/3

+ 24a

2/3

+ 8a + 32a

1/3

+ 16

28. 8a

3/2

+ a + 24a + 32a

1/2

+ 16

30.

C.
16

15

31. x + 8x + 28x

14

28

27

26

6 2

12

11

10

6 2

42

41

40 2

93

92

91 2

20

18 2

16 4

7

41. y + 7y + 21y

28

26 2

24 4

8

42. y +